DEAD box RNA helicases are pervasive protein kinase interactors and activators - Hirth, Alexander; Fatti, Edoardo; Netz, Eugen; Acebron, Sergio P.; Papageorgiou, Dimitris; Švorinić, Andrea; Cruciat, Cristina-Maria; Karaulanov, Emil; Gopanenko, Alexandr; Zhu, Tianheng; Sinning, Irmgard; Krijgsveld, Jeroen; et al. (Genome Research, 2024)
DEAD box (DDX) RNA helicases are a large family of ATPases, many of which have unknown functions. There is emerging evidence that besides their role in RNA biology, DDX proteins may stimulate protein kinases. To investigate if protein kinase–DDX interaction is a more widespread phenomenon, we conducted three orthogonal large-scale screens, including proteomics analysis with 32 RNA helicases, protein array profiling, and kinome-wide in vitro kinase assays. We retrieved Ser/Thr protein kinases as prominent interactors of RNA helicases and report hundreds of binary interactions. We identified members of ten protein kinase families, which bind to, and are stimulated by, DDX proteins, including CDK, CK1, CK2, DYRK, MARK, NEK, PRKC, SRPK, STE7/MAP2K, and STE20/PAK family members. We identified MARK1 in all screens and validated that DDX proteins accelerate the MARK1 catalytic rate. These findings indicate pervasive interactions between protein kinases and DEAD box RNA helicases, and provide a rich resource to explore their regulatory relationships.